Prospective instrumental evaluation of swallowing, tongue function, and QOL measures following transoral robotic surgery alone without adjuvant therapy. Issue 2 (15th December 2018) - Lazarus, Cathy L.; Ganz, Cindy; Ru, Meng; Miles, Brett A.; Kotz, Tamar; Chai, Raymond L.
Abstract: Background: Transoral robotic surgery (TORS) has been utilized to deintensify treatment. No studies have measured swallow safety and efficiency, nor assessed the functional impact of TORS alone. Methods: This prospective cohort underwent baseline and 1‐month postsurgery assessments including modified barium swallow evaluation, using the Dynamic Imaging Grade of Swallowing Toxicity (DIGEST) rating system, tongue range of motion assessment, the Performance Status Scale (PSS), and quality of life with the MD Anderson Dysphagia Inventory (MDADI). Results: All DIGEST safety scores were 0 (normal) at both time points. DIGEST efficiency scores were mildly impaired in 2 of 10 patients postsurgery. PSS scores revealed all patients were on regular diets, were 100% understandable, and were eating in public at both time points. Tongue Range of Motion scores were 100 of 100 at both time points. MDADI scores were not significantly different across time points. Conclusions: Careful identification of patients can result in excellent outcomes following TORS. Future studies will examine longer follow‐up of speech, swallowing, and tongue function in patients undergoing TORS surgery.